Polygodial, a drimane sesquiterpenoid dialdehyde purified from Drimys winteri, inhibits voltage-gated sodium channels. Issue 24 (17th December 2022) - Paz, Cristian; Ortiz, Leandro; Deuis, Jennifer R.; Vetter, Irina
Abstract: Drimys winteri J.R.Forst. & G.Forst, a South American evergreen shrub that is used by the Mapuche people for treatment of several painful conditions, contains polygodial, a lipophilic drimane-type sesquiterpene dialdehyde with known activity at transient receptor potential channel family members including TRPA1 and TRPV1. We sought to assess the activity of polygodial at NaV 1.7 and NaV 1.8, two key isoforms of the voltage-gated sodium channel family involved in nociception. Polygodial was isolated from D. winteri by thin-layer chromatography and analysed structurally by 1 D and 2 D nuclear magnetic resonance (NMR) spectroscopy. Activity at heterologously expressed NaV 1.7 and NaV 1.8 was assessed using automated whole-cell patch-clamp electrophysiology. Here, we show that polygodial inhibits members of the voltage-gated sodium channel family, specifically NaV 1.7 and NaV 1.8, without changing the voltage-dependence of activation or inactivation. Activity of polygodial at voltage-gated sodium channels may contribute to the previously reported antinociceptive properties. GRAPHICAL ABSTRACT: UF0001